UJI KOMPARASI LIKUIDITAS, PROFITABILITAS DAN SOLVABILITAS SEBELUM DAN SESUDAH AKUISISI (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BEI PERIODE 2012-2013) - Maleakhi Fernandes; Patricia Diana (Ultima Accounting : Jurnal Ilmu Akuntansi, 2019)
This research aims to examine the difference of liquidity, profitability and solvability of company in Indonesia Stock Exchange at timeline 2012-2013 except financial sector before and after acquisition. Liquidity is measured using Current Ratio, profitability is measured using Return on Asset Ratio, Return on Equity Ratio and Net Profit Margin Ratio, and solvability is measured using Debt to Total Asset Ratio and Debt to Total Equity Ratio. This research uses various companies’ data which listed in Indonesia Stock Exchange except financial sector and done acquisition in period 2012-2013. Samples of the research are taken by purposive sampling method. Samples that comply with the research criteria are five companies. Test for normality using Kolmogorov Smirnov method and test for hypothesis use Paired Sample t-test method if data normally distributed and Wilcoxon Signed Rank test if data not normally distributed. Result from test indicated there’s no significant difference for liquidity that measured by Current Ratio, profitability that measured by Return on Asset Ratio, Return on Equity Ratio and Net Profit Margin Ratio, solvability that measured by Debt to Total Asset Ratio and Debt to Total Equity Ratio.